2016
DOI: 10.1111/anae.13710
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care medicine in rural sub‐Saharan Africa

Abstract: Summary We undertook an audit in a rural Ugandan hospital that describes the epidemiology and mortality of 5147 patients admitted to the intensive care unit. The most frequent admission diagnoses were postoperative state (including following trauma) (2014/5147; 39.1%), medical conditions (709; 13.8%) and traumatic brain injury (629; 12.2%). Intensive care unit mortality was 27.8%, differing between age groups (p < 0.001). Intensive care unit mortality was highest for neonatal tetanus (29/37; 78.4%) and lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 14 publications
4
44
1
Order By: Relevance
“…Anaesthetic capacity is extremely limited in Uganda, with currently approximately 70 physician anaesthetists and 430 non‐physician anaesthetists serving a population of almost 40 million . The field of anaesthesia encompasses not simply the delivery of intra‐operative anaesthesia but also pain control, critical care and improvement of peri‐operative safety . The use of ultrasound‐guided regional anaesthesia may both stimulate professional development, and allow anaesthetists to engage with their surgical and nursing colleagues to promote analgesia beyond the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…Anaesthetic capacity is extremely limited in Uganda, with currently approximately 70 physician anaesthetists and 430 non‐physician anaesthetists serving a population of almost 40 million . The field of anaesthesia encompasses not simply the delivery of intra‐operative anaesthesia but also pain control, critical care and improvement of peri‐operative safety . The use of ultrasound‐guided regional anaesthesia may both stimulate professional development, and allow anaesthetists to engage with their surgical and nursing colleagues to promote analgesia beyond the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…It is limited in its capability for neurosurgical care, with no CT available, and death from TBI remains high, second only to sepsis as the overall cause of death in the hospital in 2017. A 2017 study of all admissions to the ICU in St Mary's Hospital found the mortality rate amongst patients with severe TBI to be 16·3 per cent, but the causes were not explored.…”
Section: Introductionmentioning
confidence: 99%
“…The GCS is a 3-15-point scale, assessing the patient's conscious level and neurological functioning 5 . A GCS score of 13-15 is defined as mild, [9][10][11][12] as moderate, and 3-8 as severe.…”
Section: Introductionmentioning
confidence: 99%
“…I congratulate Dunser et al. for gathering such a valuable dataset from a rural Ugandan hospital . Such epidemiological data is vital in trying to improve the care of critically ill patients in low to middle‐income countries.…”
mentioning
confidence: 99%